Generation of ultralarge Surface Enhanced Raman Spectroscopy (SERS)-active hot-spot volumes by an array of 2D nano-superlenses - Wei, Kho Kiang (2013)
Surface Enhanced Raman Spectroscopy (or SERS) has received tremendous attention in the past three decades. However, the extremely-confined probe volume (1 nm) of the plasmonic hot-spots occurring on a conventional roughened SERS-active metallic surface has limited value in macro-molecular studies. In this article, we show the plausibility of generating large SERS hot-spot volumes on an atomically-flat metal surface based upon a special 3D adiabatic plasmonic nano-focusing effect brought about by an array of nano-scale superlenses. We experimentally demonstrate the feasibility of this particular approach and report, for the first time, the acquisition of whole-protein SERS spectra of a layer of test protein, Cytochrome-c, using a custom-made Otto-Raman spectroscopy system equipped with nano-fluidics. Our study shows the potential of whole-protein SERS spectroscopy as a useful analytical tool that complements surface probe microscopies.